Phase 3 study of subcutaneous bortezomib, thalidomide, and prednisolone consolidation after subcutaneous bortezomib-based induction and autologous stem cell transplantation in patients with previously untreated multiple myeloma: the VCAT study. Issue 9 (29th July 2019) - Horvath, Noemi; Spencer, Andrew; Kenealy, Melita; Joshua, Douglas; Campbell, Philip J; Lee, Je-Jung; Hou, Jian; Qiu, Lugui; Kalff, Anna; Khong, Tiffany; Londhe, Anil; Siggins, Sarah; et al.
Abstract: Efficacy and safety of bortezomib-based consolidation following ASCT were investigated in newly diagnosed multiple myeloma patients from Australia, Korea, and China. Patients received three cycles of bortezomib-cyclophosphamide-dexamethasone induction followed by high-dose therapy/ASCT, then were randomized (1:1) to consolidation with TP (thalidomide 100 mg/d for ≤12 months/until disease progression; prednisolone 50 mg on alternate days indefinitely/until disease progression; n  = 100) or VTP (subcutaneous bortezomib 1.3 mg/m 2 every 2 weeks for 32 weeks, plus TP; n  = 103). The hypothesized difference in CR + VGPR rate (after ≤12 months consolidation therapy) was not met. The rate of CR + VGPR was numerically higher with VTP versus TP; however, this was not statistically significant (85.7% versus 77.1%; rate difference 8.6%; 95% confidence interval −2.3%–19.5%; p  = .122). Secondary efficacy outcomes were similar between treatment arms. Addition of bortezomib to TP consolidation was associated with limited additional toxicity but did not significantly improve efficacy versus TP. Trial registration: ClinicalTrials.gov identifier: NCT01539083.